2007
DOI: 10.1124/mol.107.042184
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of Adenylyl Cyclase-Related Signaling Sequelae after Long-Term Morphine Treatment

Abstract: Adaptations to long-term morphine treatment resulting in tolerance are protective by counteracting the consequences of sustained opioid receptor activation. Consequently, the manifestation of specific adenylyl cyclase (AC)-related neurochemical sequelae of long-term morphine treatment should depend on the consequences of short-term -opioid receptor (MOR) activation. We tested this by comparing complementary chemical sequelae of long-term morphine treatment among cells in which short-term MOR activation inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
(75 reference statements)
1
12
0
1
Order By: Relevance
“…We had reported previously that chronic morphine increases MOR G s coupling in cell lines as well as spinal cord (Chakrabarti et al, 2005a;Chakrabarti and Gintzler, 2007;Shy et al, 2008). The present results reaffirm those findings and put them into a physiological context, i.e., enhanced MOR G s signaling during withdrawal enables opioid facilitation of EM2 release, which in turn contributes to withdrawalcoping mechanisms.…”
Section: Discussionsupporting
confidence: 79%
“…We had reported previously that chronic morphine increases MOR G s coupling in cell lines as well as spinal cord (Chakrabarti et al, 2005a;Chakrabarti and Gintzler, 2007;Shy et al, 2008). The present results reaffirm those findings and put them into a physiological context, i.e., enhanced MOR G s signaling during withdrawal enables opioid facilitation of EM2 release, which in turn contributes to withdrawalcoping mechanisms.…”
Section: Discussionsupporting
confidence: 79%
“…6). Because increased MOR G s ␣ signaling is associated with the formation of opioid tolerance (Chakrabarti et al, 2005;Chakrabarti and Gintzler, 2007;Shy et al, 2008) and caveolae are generally considered to be important subcellular domains specifying the formation of signaling complexes, understanding the caveolae-associated substrates for MOR G s ␣ AC signaling could provide unexpected insights into critical subcellular determinants of tolerance and the related phenomenon of addiction.…”
Section: Discussionmentioning
confidence: 99%
“…1) In MOR-CHO membranes, sufentanil stimulated the translocation of G s ␣ into Triton-insoluble membrane compartments. 2) Sufentanil enhanced the coimmunoprecipitation (co-IP) of G s ␣ and adenylyl cyclase (AC) with caveolin-1 (a marker for caveolae) from the Triton-insoluble membrane fraction of spinal cord Pharmacological analyses (Xu et al, 1989;Shen and Crain, 1990;Gintzler and Xu, 1991;Cruciani et al, 1993;Wang and Gintzler, 1997;Szucs et al, 2004) and biochemical analyses (Chakrabarti et al, 2005;Chakrabarti and Gintzler, 2007;Shy et al, 2008) provide convergent evidence for -opioid receptor (MOR) signaling via G s , which has been long debated among opioid researchers. Our recent demonstrations that MOR is present in G s ␣ immunoprecipitate (IP), obtained from a variety of MOR-expressing cell lines and spinal cord, and the content of MOR in G s ␣ IP increases after chronic morphine exposure underscores the putative relevance of MOR G s ␣ signaling to acute and chronic opioid responsiveness.…”
Section: Introductionmentioning
confidence: 99%
“…The complexity and multidimensionality of cellular mechanisms underlying opioid tolerance are underscored by the recent report that a subset of inter-related cell signaling adaptations to chronic morphine exposure does not represent a fixed set of adaptations; rather, these inter-related cell signaling adaptations are cell state-dependent (Shy et al, 2008).…”
Section: Dependence Of Cellular Opioid Tolerance Mechanisms On Cell Smentioning
confidence: 99%
“…The qualitative difference in the consequences of acute MOR activation (AC inhibition versus stimulation) has a profound effect on the manifestation of multiple, complementary AC-related adaptations to chronic morphine, many of which are diametrically opposite (Shy et al, 2008). It is striking that none of the AC/cAMP-related adaptations to chronic morphine observed in MOR-CHO and AC1-MOR-CHO (increased AC and G ␤ phosphorylation, membrane protein kinase C␥ translocation and MOR G s association (Chakrabarti et al, 1998b(Chakrabarti et al, , 2005aChakrabarti and Gintzler, 2003) is observed in AC2-MOR-CHO.…”
Section: Dependence Of Cellular Opioid Tolerance Mechanisms On Cell Smentioning
confidence: 99%